Diagnostic Accuracy of Transcerebellar Diameter for Gestational Age - RuqyyahSalim, Sobia Nawaz, Farzana Kazmi (Journal of Rawalpindi Medical College, 2017)
To determine the correlation of mean transcerebellar diameter and mean gestational age in third trimester of pregnancy Methods: In this cross sectional study all pregnant women with previous regular menstrual period aged 25-35 years, gestational age between 26 to 38 weeks assessed on LMP and having single fetus assessed on ultrasound were enrolled. Ultrasound measurements of TCD (in mm) were made. Results: Mean age of the patients was 29.53 ±3.60 years. Mean gestational age of the patients was 32.56 ±3.51 weeks. There were 61% nulliparous and 39% multiparous women. Spearman’s Correlation test was applied to see the relationship of TCD with gestational age. Strong positive correlation was observed (rho 0.968, p-value <0.001). Conclusion: Strong positive correlation of mean transcerebellar diameter and mean gestational age is observed in third trimester of pregnancy